2013
DOI: 10.1039/c2nr33595f
|View full text |Cite
|
Sign up to set email alerts
|

Novel hollow Pt-ZnO nanocomposite microspheres with hierarchical structure and enhanced photocatalytic activity and stability

Abstract: Noble metal/semiconductor nanocomposites play an important role in high efficient photocatalysis. Herein, we demonstrate a facile strategy for fabrication of hollow Pt-ZnO nanocomposite microspheres with hierarchical structure under mild solvothermal conditions using Zn (CH(3)COO)(2)·2H(2)O and HPtCl(4) as the precursors, and polyethylene glycol-6000 (PEG-6000) and ethylene glycol as the reducing agent and solvent, respectively. The as-synthesized ZnO and Pt-ZnO composite nanocrystals were well characterized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
166
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 323 publications
(172 citation statements)
references
References 71 publications
4
166
0
2
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11] Understanding the catalysis mechanism is vital for the design of new functional materials to be a part of an environmentally friendly technology. The catalytic process on the surface of a semiconductor has been proposed by Izumi et al 12 and Matthews.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Understanding the catalysis mechanism is vital for the design of new functional materials to be a part of an environmentally friendly technology. The catalytic process on the surface of a semiconductor has been proposed by Izumi et al 12 and Matthews.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that delaying the recombination of photogenerated electron-hole pair increases the efficiency of the catalysts [10,12,[15][16][17][18][19][20][21][22][23]. On the other hand, the efficiency of the catalyst is dependent on the crystal-phase [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…This not only minimizes the usage of catalyst but also enhances the active sites on the surface [10][11][12][13]18]. One should note that other significant attempts of enhancing the photocatalytic activity (PCA) or delaying the recombination are lattice defects [12,16,[18][19][20][21][22][23], heterojunctions [4,10,[14][15][16][17][24][25][26] etc. It is also notable that PCA is a very complex process and it is an integral effect of surface sites, bulk of the lattice etc.…”
Section: Introductionmentioning
confidence: 99%
“…Boppella et al [1] reported the formation of oriented ZnO structures with tunable percentage of exposed polar facets via a simple hydrothermal route in aqueous base environment. Yu et al [2] demonstrated unique hollow Pt-ZnO nanocomposite microspheres with hierarchical structure under mild solvothermal conditions. Especially, this method has an advantage for the synthesis of graphene-based nanomaterials due to the possible synchronous reduction of graphene oxide and the corresponding metal precursors [3,4].…”
Section: Introductionmentioning
confidence: 99%